Research on alkali metal-modified Pd catalyst for oxygen removal from propylene - Zhao, Jinchong; Jiang, Jie; Wen, Song; Zhang, Jing; Zhang, Changsheng; Sheng, Nan; Liang, Wei; Sun, Bing; Xu, Wei; Yang, Zhe; Pan, Yuan (Frontiers in Chemistry, 2022)
A series of alkali metals (Li, Na, K) modified Pd catalysts and Pd/Al2O3 were prepared and used to remove oxygen in a propylene flow with hydrogen exist. The results showed that the alkali metals could enhance the performance of the Pd catalysts and the effect followed the order of K > Na > Li. X-Ray diffraction (XRD), N2-physisorption, transmission electron microscope (TEM), Hydrogen temperature programmed reduction (H2-TPR), X-ray photoelectron spectroscopy (XPS) were carried out to investigate the alkali metal modified Pd catalysts and the promotion effect mechanism was explained. The results showed that alkali metal modification increased the electron density of Pd atoms to induce the negatively charged Pd species, which could enhance the adsorption of oxygen while weaken the adsorption of propylene, and then enhanced the performance of the modified catalysts for oxygen removal from unsaturated hydrocarbon. The Pd-K/A catalyst performed the best on both oxygen removal and propylene hydrogenation inhibition.